Analisis Kinerja Pelayanan Publik tentang Sumber Daya Manusia dan Responsivitas Pegawai di Kantor Kelurahan Kecandran Kecamatan Sidomukti Kota Salatiga - Muchamad Samsudin (Mahesa Research Center, 2021)
This article or writing aims to provide an effective understanding of the analysis of the performance of public services in Kecandran Village, Siomukti District, the problem is focused on a more in-depth analysis of public service activities in Kecandran Village and examine the form of responsiveness carried out by employees and related parties in the service. In order to approach this problem, Nicholas Henry's theoretical reference is used (in Suwitri, 2011), Carl Van Horn dan Donal Van Meter, 1975. The data were collected through descriptive research methods through field observations, primary and secondary data and interviews, and analyzed qualitatively. This study concludes that it is necessary to conduct research related to the analysis of the performance of public services at the Kecandran sub-district office, Sidomukti District which is more in-depth on human resources and responsiveness.